2009
DOI: 10.1016/j.eurpsy.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and time perspective in high school students

Abstract: Differences in time perspective dimensions between moderate and severe ideators suggest that these groups should be considered and analyzed as two discrete groups in further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
51
1
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 27 publications
(44 reference statements)
4
51
1
13
Order By: Relevance
“…Time perspective may also be associated with risky HIV infection practices (Rothspan and Read 1996). A negative past or a fatalistic present have been found to predict suicidal ideation in high school students (Laghi et al 2009a), while a past-negative time perspective may significantly mediate depressive symptoms in adolescent cancer survivors (Bitsko et al 2008). Higher levels of depression and anxiety were also predicted by higher negative perceptions of the past in individuals diagnosed with chronic diseases such as diabetes (Livneh and Martz 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Time perspective may also be associated with risky HIV infection practices (Rothspan and Read 1996). A negative past or a fatalistic present have been found to predict suicidal ideation in high school students (Laghi et al 2009a), while a past-negative time perspective may significantly mediate depressive symptoms in adolescent cancer survivors (Bitsko et al 2008). Higher levels of depression and anxiety were also predicted by higher negative perceptions of the past in individuals diagnosed with chronic diseases such as diabetes (Livneh and Martz 2007).…”
Section: Introductionmentioning
confidence: 97%
“…This subscale is related to depression, anxiety, and aggression. Laghi et al (2009) and Van Beek et al (2010) also found that higher scores in the present fatalistic orientation are associated with less extraversion, consciousness, higher neuroticism, and an increased risk of suicidal ideation.…”
mentioning
confidence: 92%
“…For example, individuals who are strongly biased toward the present might not consider the future consequences of their acts by decreasing risk perception of behaviors such as smoking, substance use, or physical inactivity (e.g., Adams & Nettle, 2009;Apostolidis, Fieulaine, Simonin, & Rolland, 2006;Boyd & Zimbardo, 2005;Daugherty & Brase, 2010). The relevance of a biased TP in abnormal psychological functioning has also been suggested by several authors indicating that TP could be considered a core feature of some psychiatric disorders such as depression and suicidal ideation (Laghi, Baiocco, D'Alessio, & Gurrieri, 2009;van Beek, Berghuis, Kerkhof, & Beekman, 2011). Zimbardo and Boyd (1999) described five temporal frames, i.e., Past-Negative, Present-Hedonistic, Future, PastPositive and Present-Fatalistic through theoretical conceptualization and factorial analysis and developed the Zimbardo Time Perspective Inventory (ZTPI).…”
Section: Introductionmentioning
confidence: 99%